Short video news: development, current situation and prospects - Xingyu, Chen (Journal of the Belarusian State University. Journalism, 2026)
This article examines the specifics, advantages, and limitations of short video news distribution, focusing on Chinese, Belarusian, and European experiences. It analyses the practical activities of bloggers and television channels in creating short video news. It examines the challenges in this area and potential development paths for short video content. It explores the essence of the interactive and symbiotic interaction between new and traditional media during the digital transition, focusing on ways to adapt to these changes.
Keywords: short videos; short video news; bloggers; television channels; distribution form; social network; digital media; user; content; news